Movimentos Sociais e Rádio Comunitária: estudo sobre a Práxis e o Projeto do Movimento de Radiodifusão Comunitária em Alagoas entre 1999 e 2006 - SANTOS, Bruno Silva dos (2006)
This dissertation presents a study concerning both the project and the praxis of Communitarian Broadcasting Movements in Alagoas. The analysis has shown that group actions evolving communitarian radios, in the up mentioned state, represent a clear expression of the Brazilian social movements. Moreover, the initial difficulties faced by free radios, later, communitarian radios relate to class struggle in the Brazilian capitalist system. The aim of this research is to investigate those mentioned group actions, in order to unveil the actions of the Brazilian Movement of Communitarian Broadcasting (BMCB) in Alagoas, from its upsurge to the current days. It has also the aim of analyzing the relations between the Brazilian State, the social movements and the public politics, questioning the possibility of finding in the local movement a project whose praxis were a means to that end. Therefore, the dialectic method has been used so that one can understands the social-historical movement in its totality. We have made a bibliographical research, from both documental research and field research with the technique of half-structuralized interview. That way, it became possible to theorize the foundations of BMCB in Alagoas and identify the following components of social movements: the democratization of communication as a project and the spreading of communitarian broadcasting experiences as a possible praxis. However, it is of relevance to point to the barriers and objections imposed by the capitalist system to the studied movements. We intend to contribute with the effectiveness of the right for communication, as both a social and human right in the national scenario and, especially, in the local scope.